A Call for New Communication Channels for Gynecological Oncology Trainees: A Survey on Social Media Use and Educational Needs by the European Network of Young Gynecological Oncologists. Issue 3 (March 2017) - Zalewski, Kamil; Lindemann, Kristina; Halaska, Michael J.; Zapardiel, Ignacio; Laky, Rene; Chereau, Elisabeth; Lindquist, David; Polterauer, Stephan; Sukhin, Vladislav; Dursun, Polat
Abstract : Objective: The aim of the study was to assess patterns in the use of social media (SM) platforms and to identify the training needs among European gynecologic oncology trainees. Methods: In 2014, a web-based survey was sent to 633 trainees from the European Network of Young Gynaecological Oncologists (ENYGO) database. The 14-item questionnaire (partially using a 1- to 5-point Likert scale) assessed respondents' use of SM and preference for workshop content and organization. Descriptive analysis was used to describe the mean scores reported for different items, and the internal reliability of the questionnaire was assessed by Cronbach α. Results: In total, 170 ENYGO members (27%) responded to the survey. Of those, 91% said that they use SM platforms, mostly for private purposes. Twenty-three percent used SM professionally and 43% indicated that they would consider SM to be a clinical discussion forum. The respondents said that they would like updates on conferences and professional activities to be shared on SM platforms. Complication management, surgical anatomy, and state of the art in gynecologic oncology were identified as preferred workshops topics. The most frequently indicated hands-on workshops were laparoscopic techniques and surgical anatomy. Consultants attached a higher level of importance to palliative care education and communication training than trainees. The mean duration of the workshop preferred was 2 days. Conclusions: This report highlights the significance of ENYGO trainees' attachment to SM platforms. Most respondents expect ENYGO to use these online channels for promoting educational activities and other updates. Using SM for clinical discussion will require specific guidelines to secure professional and also consumer integrity. This survey confirms surgical management and the state of the art as important knowledge gaps, and ENYGO has tailored its activities according to these results. Future activities will further direct attention and resources to education in palliative care and molecular tumor biology.